Novel anti-angiogenic therapeutic strategies in colorectal cancer. (3rd May 2016) - Tampellini, M.; Sonetto, C.; Scagliotti, G. V.
ABSTRACT: Introduction : Anti-angiogenetic agents are currently the standard of care in metastatic CRC patients. Bevacizumab, aflibercept, regorafenib and recently ramucirumab have significantly improved both progression-free and overall survival in different lines of treatment. Since bevacizumab's approval, a number of novel anti-VEGF agents have been tested in preclinical and clinical models. Areas covered : This review is focused on the most recent clinical results of novel agents targeting VEGF and its receptors with a major focus on those investigated recently in clinical trials. Expert opinion : In the last 15 years, a number of new anti-angiogenetic agents have been tested. Unfortunately, most of them have demonstrated unacceptable toxicities or failed to show activity. When tested as single agents, encouraging preliminary results were reported with fruquintinib, famitinib, and nintedanib. Interesting novel mechanisms of action are also being explored: VGX-100 is a monoclonal antibody (mAb) which binds to VEGF-C, inhibiting activation of VEGFR-2 and VEGFR-3 when combined with bevacizumab; tanibirumab is a mAb which binds to VEGFR-2 and vanucizumab is a bispecific mAb binding both to VEGF-A and Angiopoietin-2. Data about the combination of these agents with chemotherapy are very encouraging, even though preliminary. However, the definition of specific predictive biomarkers remains a priority.